The restriction endonuclease Tru9I is a useful tool to analyze telomere sequences separately from interstitial telomeric sequences in Arabidopsis thaliana - Vaquero-Sedas, María I.; Vega-Palas, Miguel A. (Scientific Research Publishing, 2012)
We have previously described a simple method to analyze the chromatin structure of Arabidopsis telomeres independently of that of Interstitial Telomeric Sequences (ITSs). By using this method, we found that, whereas ITSs are heterochromatic, Arabidopsis telomeres exhibit euchromatic features [1]. Some concerns have been recently raised about the accuracy of this procedure [2]. Here, we summarize these concerns and justify our experimental approaches and interpretation of results.
Keywords: Arabidopsis thaliana; telomeres; ITSs; euchromatin; heterochromatin